Assessing the assessments: evaluation of four impact assessment protocols for invasive alien species - Turbé, Anne; Pârâu, Liviu G. (Diversity & distributions, 2017)
Aim: Effective policy and management responses to the multiple threats posed by invasive alien species (IAS) rely on the ability to assess their impacts before conclusive empirical evidence is available. A plethora of different IAS risk and/or impact assessment protocols have been proposed, but it remains unclear whether, how and why the outcomes of such assessment protocols may differ. Location: Europe. Methods: Here, we present an in-depth evaluation and informed assessment of the consistency of four prominent protocols for assessing IAS impacts (EICAT, GISS, Harmonia+ and NNRA), using two non-native parrots in Europe: the widespread ring-necked parakeet (Psittacula krameri) and the rapidly spreading monk parakeet (Myiopsitta monachus). Results: Our findings show that the procedures used to assess impacts may influence assessment outcomes. We find that robust IAS prioritization can be obtained by assessing species based on their most severe documented impacts, as all protocols yield consistent outcomes across impact categories. Additive impact scoring offers complementary, more subtle information that may be especially relevant for guiding management decisions regarding already established invasive alien species. Such management decisions will also strongly benefit from consensus approaches that reduce disagreement between experts, fostering the uptake of scientific advice into policy-making decisions. Main conclusions: Invasive alien species assessments should take advantage of the capacity of consensus assessments to consolidate discussion and agreement between experts. Our results suggest that decision-makers could use the assessment protocol most fit for their purpose, on the condition they apply a precautionary approach by considering the most severe impacts only. We also recommend that screening for high-impact IAS should be performed on a more robust basis than current ad hoc practices, at least using the easiest assessment protocols and reporting confidence scores.
Gesehen am 17.09.2018